Multi-type solitary wave solutions of Korteweg-de Vries (KdV) equation - Waheed, Asif; İnç, Mustafa; Bibi, Nimra; Javeed, Shumaila; Zeb, Muhammad; Zafar, Zain Ul Abadin (World Scientific Publ Co Pte Ltd, 2024)
In this paper, we explore how to generate solitary, peakon, periodic, cuspon and kink wave solution of the well-known partial differential equation Korteweg-de Vries (KdV) by using exp-function and modified exp-function methods. The presented methods construct more efficiently almost all types of soliton solution of KdV equation that can be rarely seen in the history. These methods appear to be straightforward and symbolic calculations are used to solve the problem. All resulting answers are verified for accuracy using the symbolic computation program with Maple. To show the physical appearance of the model, 3D plots of all the generated solutions are then displayed. The obtained solutions revealed the compatibility of the proposed techniques which provide the general solution with some free parameters. This is the key benefit of these methods over the other methods.
Keywords: Korteweg-de Vries (KdV); cuspon; kink wave; peakon; solitary wave; exp-function method